Study on the evaluation and influencing factors of contracted residents on the coordination of primary medical institutions - Xu, Lingfeng; Xu, Na; Jiang, Xiaoli; Peng, Haibo; Wu, Yixuan; Lang, Zihan; Zhou, Lifang; Ma, Dongping; Chen, Zhongming; Yin, Chengliang; Yu, Qianqian (Frontiers in Public Health, 2024)
Background The implementation of family doctor contract service is a pivotal measure to enhance primary medical services and execute the hierarchical diagnosis and treatment system. Achieving service coordination among various institutions is both a fundamental objective and a central element of contract services. Objective The study aims to assess residents’ evaluations and determining factors related to the coordination of health services within primary medical institutions across different regions of Shandong Province. The findings intend to serve as a reference for enhancing the coordination services offered by these institutions. Methods The study employed a multi-stage stratified random sampling method to select three prefecture-level cities in Shandong Province with different economic levels. Within each city, three counties (districts) were randomly sampled using the same method. Within each county (district), three community health service centers and township health centers implementing family doctor contract services were selected randomly. Face-to-face questionnaire surveys were conducted with contracted residents using the coordination dimension of the revised Primary Care Assessment Tools Scale (PCAT) developed by the research team. Data analysis was conducted using such methods as one-way analysis of variance and multiple linear regression. Results The sample included 3,859 contracted residents. The coordination dimension score of primary medical institutions averaged 3.41 ± 0.18, with the referral service sub-dimension scoring 3.60 ± 0.58 and the information system sub-dimension scoring 3.34 ± 0.65. The overall score of the referral service sub-dimension surpassed that of the information system sub-dimension. Regression results indicated that the city’s economic status, the type of contracted institutions, gender, education, marital status, income, occupation, health status, and endowment insurance payment status significantly influenced the coordinated service score of primary medical institutions (p < 0.05). Conclusion The coordination of primary medical institutions in Shandong Province warrants further optimization. Continued efforts should focus on refining the referral system, expediting information infrastructure development, enhancing the service standards of primary medical institutions, and fostering resident trust. These measures aim to advance the implementation of the hierarchical diagnosis and treatment and two-way referral system.